The Concept Of Fitrah Perspective Yasin Mohamed In Fitra's Book: The Islamic Concept Of Human Nature - Fauzi, Irfan; Hanum, Azizah; Arsyad, Junaidi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This research will explore Yasien Mohamed's Fitrah Theory, to reveal its construction and increase our knowledge about Islamic Education.The main question that will be discussed in this study is how the theory of Fitrah in Islam and Yasien Mohamed's view of nature itself and how this analysis can contribute to the development of Islamic education.The research methodology used is a descriptive and analytical library research method, and the analysis uses content analysis. The main source of this study is Yasien Muhammad's book, Fitrah: The Islamic Concept of Human Nature, which explores his research findings on God's role in giving human nature potential. It was revealed that God acted as the initial cause and passed down the fitrah through genetic inheritance.Based on the Fitrah Theory, the construction of Islamic Education can function as a countermeasure for secularism in the field of Islamic education, and aims to form individuals who have high moral values and character, as guided by the Al-Qur'an.